Self-assembled micelles of novel amphiphilic copolymer cholesterol-coupled F68 containing cabazitaxel as a drug delivery system - Song Y (Dove Medical Press, 2014)
Yanzhi Song,1 Qingjing Tian,1 Zhenjun Huang,1 Di Fan,1 Zhennan She,1 Xinrong Liu,1 Xiaobo Cheng,1 Bin Yu,2 Yihui Deng11College of Pharmacy, Shenyang Pharmaceutical University, 2Liaoning Medical Device Test Institute, Shenyang, People’s Republic of ChinaAbstract: Despite being one of the most promising amphiphilic block copolymers, use of Pluronic F68 in drug delivery is limited due to its high critical micelle concentration (CMC). In this study, we developed a novel F68 derivative, cholesterol-coupled F68 (F68-CHMC). This new derivative has a CMC of 10 µg/mL, which is 400-fold lower than that of F68. The drug-loading capacity of F68-CHMC was investigated by encapsulating cabazitaxel, a novel antitumor drug. Drug-loaded micelles were fabricated by a self-assembly method with simple dilution. The optimum particle size of the micelles was 17.5±2.1 nm, with an entrapment efficiency of 98.1% and a drug loading efficiency of 3.16%. In vitro release studies demonstrated that cabazitaxel-loaded F68-CHMC micelles had delayed and sustained-release properties. A cytotoxicity assay of S180 cells showed that blank F68-CHMC was noncytotoxic with a cell viability of nearly 100%, even at a concentration of 1,000 µg/mL. The IC50 revealed that cabazitaxel-loaded F68-CHMC micelles were more cytotoxic than Tween 80-based cabazitaxel solution and free cabazitaxel. In vivo antitumor activity against S180 cells also indicated better tumor inhibition by the micelles (79.2%) than by Tween 80 solution (56.2%, P<0.05). Based on these results, we conclude that the F68-CHMC copolymer may be a potential nanocarrier to improve the solubility and biological activity of cabazitaxel and other hydrophobic drugs.Keywords: Pluronic F68, cholesterol, synthesis, cabazitaxel, micelles, cancer therapy